2014
DOI: 10.3989/ic.13.021
|View full text |Cite
|
Sign up to set email alerts
|

Análisis plástico y Ensayos de Losas multidireccionales de HRFA

Abstract: Licencia/License: Salvo indicación contraria, todos los contenidos de la edición electrónica de Informes de la Construcción se distribuyen bajo una licencia de uso y distribución Creative Commons Reconocimiento no Comercial 3.0. España (cc-by-nc).Cómo citar este artículo/Citation: Maturana, A., Canales, J., Orbe, A., Cuadrado, J. (2014 RESUMENEn este trabajo se realiza un estudio teórico-experimental de losas multidireccionales de hormigón reforzado con fibras de acero (HRFA). El estudio se enmarca en una apl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…In already constructed HRC flat slabs, generally, the absence of cracking under quasi‐permanent load combinations was pointed out which permitted to evaluate the produced deformations as for an isotropic linear elastic material 15,25 . However, the presence of cracks in this type of elements is expectable—in accordance with ACI 421.3R‐15, microcraking in two‐way concrete slabs starts at an early level of approximately 10% of the service load, whereas the pattern of potential yield lines is almost fully developed at 30% of the same load 57…”
Section: Proposed Design Approachmentioning
confidence: 99%
“…In already constructed HRC flat slabs, generally, the absence of cracking under quasi‐permanent load combinations was pointed out which permitted to evaluate the produced deformations as for an isotropic linear elastic material 15,25 . However, the presence of cracks in this type of elements is expectable—in accordance with ACI 421.3R‐15, microcraking in two‐way concrete slabs starts at an early level of approximately 10% of the service load, whereas the pattern of potential yield lines is almost fully developed at 30% of the same load 57…”
Section: Proposed Design Approachmentioning
confidence: 99%
“…In this regard, results derived from experimental programs revealed that the use of SFRC in this structural typology leads to enhanced cracking control [1][2][3][4] and required ductility [5][6][7] to allow for stress redistribution. 1,3,4,7 The design-oriented studies in this field have proposed analytical approaches 2,[8][9][10][11][12][13] and methods based on linear elastic 14 or nonlinear [15][16][17][18][19][20][21] finite element (FE) simulations focused on the design of flexuralgoverned SFRC slabs.…”
Section: Introductionmentioning
confidence: 99%
“…This matches how real case applications have evolved, from early usage on slabs-on-grade (with very low demands) to precast tunnel segment linings (compression under service and a relatively low bending and concentrated loads during construction phases), to one of the latest use cases, elevated slabs (bending and shear are the main design forces). Recent experiences with FRC elevated slabs from real-world applications and research campaigns showed that fibers can effectively replace all (or almost all) conventional reinforcement despite the increase of internal forces compared to initial slab-on-grade loads [7][8][9].…”
Section: Introductionmentioning
confidence: 99%